ALAT PENYINARAN GERMISID ULTRAUNGU (UVGI) JENIS C BERJAYA MEMBASMI PERTUMBUHAN DAN MENGHALANG PENYEBARAN PATOGEN MELALUI FOMIT: THE ULTRAVIOLET GERMICIDAL IRRADIATION (UVGI) TYPE C IRRADIATION DEVICE IS EFFECTIVE IN ERADICATING GROWTH AND PREVENTING THE TRANSMISSION OF PATHOGENS VIA FOMITES (Jurnal Teknologi (Sciences & Engineering), 2024)
The emergence of hospital-acquired or nosocomial infection caused by ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter sp.) that are resistant to antibiotics poses public healthcare concern. Transmission of the pathogens to patients and healthcare workers can occur through various types of fomites. Pathogens can be eradicated by using UV radiation type C (UVC). In this work, several fomite samples (cloth, paper, skin, and plastic) have been contaminated with pathogens. They were then irradiated with UVC using LembayUVng®. The effectiveness was quantitatively evaluated by comparing the bacterial growth on the formite samples before and after irradiation. The results show that UVC radiation has 90-100% average efficiency in pathogen eradication against several different strains. This study provides valuable information on selection of effective method for infection control.